Implementasi Terapi Bermain Mewarnai sebagai Intervensi Keperawatan Nonfarmakologis dalam Menurunkan Kecemasan Anak Usia Prasekolah Selama Hospitalisasi - Mochammad Ilham Setya; Alvi Ratna Yuliana; Luluk Cahyanti; Vera Fitriana; Yulia Ardiyanti (Institut Teknologi Kesehatan Cendekia Utama Kudus, 2026)
Hospitalization can be an anxiety-provoking experience for preschool children due to unfamiliar hospital environments, medical procedures, and separation from parents. If not appropriately managed, anxiety may affect children’s comfort, emotional adaptation, and cooperation during the care process. Therefore, applicable non-pharmacological nursing interventions are required, one of which is coloring play therapy.This study aimed to evaluate the implementation of coloring play therapy in helping reduce anxiety levels among hospitalized preschool children. A pre-experimental design with a descriptive applied approach was used, consistent with the characteristics of vocational nursing education (Diploma in Nursing). The participants consisted of 15 hospitalized children aged 3–6 years. Anxiety levels were assessed using the Face Image Scale (FIS) before and after a single session of coloring play therapy lasting 15–30 minutes.The results showed that prior to the intervention, all participants experienced moderate to severe anxiety, with 9 children (60.0%) classified as having severe anxiety and 6 children (40.0%) moderate anxiety. Following the implementation of coloring play therapy, a clinical reduction in anxiety was observed, indicated by the absence of severe anxiety and a shift toward milder anxiety categories, where 12 children (80.0%) were classified as very not anxious, not anxious, or mildly anxious.Conclusion: Coloring play therapy can be applied as a clinically effective non-pharmacological nursing intervention to help reduce anxiety among hospitalized preschool children and support practice-based pediatric nursing care.